Karakteristik Fisik Perairan Selatan Kabupaten Kepulauan Tanimbar pada Musim Transisi II - Wattimena, Marlin Chrisye; Ratuluhain, Eva Susan; Tubalawony, Simon (Prodi Ilmu Kelautan Fakultas Perikanan dan Ilmu Kelautan Universitas Pattimura, 2023)
This study investigated the characteristics of stratification and vertical stability of southern waters of Tanimbar Islands Regency. CTD Data from World Ocean Database 2018 especially November 1995 to represent second transitional season were utilized in this study. The CTD data were processed using Ocean Data View. This study showed that vertically the temperature of the surface layer ranged between 29 to 30 oC and the thickness of surface mixed layer was found to be 44 m. The thermocline layer has temperature ranging between 12 to 28 oC and a maximum depth of 306 m. Below thermocline layer temperature reduced to reach less than 7 oC (depth > 500 m). On the halocline layer, a high saline water was found between 66 - 94 m depth and was located on the southern part between Barbar Islands and Tanimbar Islands. Water mass was found to be unstable in the mixing layer.